Penerapan Green Accounting dan Corporate Social Responsibility Disclosure Terhadap Nilai Perusahaan Melalui Profitabilitas - Catur Muhammad Erlangga; Achmad Fauzi; Ati Sumiati (Department of Accounting-Faculty of Economic and Business (FEB), 2021)
This study aims to provide an overview of Green Accounting, disclosure of corporate social responsibility, company profitability and company value in manufacturing companies listed on the Indonesia Stock Exchange in 2019. The research method used is quantitative method with descriptive and verification methods. The sample of this research is 200 manufacturing companies listed on the Indonesia Stock Exchange in 2019. The data analysis method used in this study is the expansion path analysis of simple and multiple regression analysis, single test, multiple correlation coefficient (R) analysis, and coefficient of determination. While the hypothesis testing used is the statistical method of partial test (t test), simultaneous test (f test) and Sobel significant test using Eviews version 10 Enterprise. The results showed that there was a positive and significant effect on the implementation of Green Accounting and Corporate Social Responsibility Disclosure on the profitability and firm value. Profitability also significantly affected firm value, but the mediating effect of the profitability variable did not occur.